Case Report: A Case Report and Literature Review on Severe Bullous Skin Reaction Induced by anti-PD-1 Immunotherapy in a Cervical Cancer Patient - Li, Xiang; Qu, Li-Xin; Ren, Yu-Mei; Hu, Chang (Frontiers in Pharmacology, 2021)
BACKGROUND Anti-programmed cell death protein 1 (PD-1) has been successfully used in carcinomas treatment. However, it causes significant adverse effects (AEs), including cutaneous reactions，particularly the life-threatening severe bullous skin reactions (SBSR) and toxic epidermal necrolysis (TEN). CASE SUMMARY Herein, we described for the first time a case report of SBSR induced by anti-PD-1 therapy in a cervical cancer patient. In addition, we revised existing literature on anti-PD-1 induced cutaneous reactions. We reported a cervical cancer patient who was treated with four successive cycles of Sintilimab and Toripalimab injections and developed systemic rashes, bullae, and epidermal desquamation, which worsened and led to infection, eventually causing death after being unresponsive to aggressive treatments. CONCLUSION Anti-PD-1 antibodies commonly cause skin toxicity effects, some of which may be deadly. Therefore, healthcare providers should observe early symptoms and administer proper treatment to prevent aggravation of symptoms.